2021
DOI: 10.3390/ijerph18063233
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of War-Related Stress on Coronary Artery Disease Severity in War Survivors: A SYNTAX Study

Abstract: Background: Due to the strong relationship between stress and heart disease, particularly acute myocardial infarction (MI), this study investigated the complexity of coronary artery disease (CAD) among Syrian refugee patients referred to Jordan University Hospital and its relation to war-related stressors. Methods: This is a retrospective study that utilized the SYNTAX I score in order to evaluate all Syrian refugees that underwent coronary artery catheterization at Jordan University Hospital during the period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Therefore, it is possible to detect a significant degree of concern among Syrians about their lack of information about CVDs. This is because Syria's educational and health care levels have been worsened following 11 years of civil war, which destroyed many hospitals and physicians' immigration to neighbouring countries to get enough resources for survival [25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible to detect a significant degree of concern among Syrians about their lack of information about CVDs. This is because Syria's educational and health care levels have been worsened following 11 years of civil war, which destroyed many hospitals and physicians' immigration to neighbouring countries to get enough resources for survival [25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…2 In the United States, studies have consistently demonstrated racial disparity in hypertension particularly among African American and Mexican-American individuals. 5 Immigrants and war refugees represent another vulnerable group [6][7][8] Exposure to humanitarian crises such as war, leads to worsening cardiovascular disease. 6 Groups that are exposed to armed conflict in low and middle income countries appear to have a higher prevalence of coronary heart disease and cerebrovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…5 Immigrants and war refugees represent another vulnerable group [6][7][8] Exposure to humanitarian crises such as war, leads to worsening cardiovascular disease. 6 Groups that are exposed to armed conflict in low and middle income countries appear to have a higher prevalence of coronary heart disease and cerebrovascular disease. 9 They are also subject to massive trauma, which can result in psychiatric disorders such as depression and posttraumatic stress disorder that can increase risk of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When it comes to chronic conditions, lessons learned from previous armed conflicts show that, in the case of Ukrainian people, other sequelae may also occur. These include a variety of stress-mediated conditions, such as exacerbations of cardiovascular diseases, strokes and heart attacks, cancers and many more, which, in turn, may lead to substantially increased mortality among civilians, including children who are burdened most severely ( Jawad et al, 2020 ; Sadetzki et al, 2017 ; Al-Makhamreh et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%